STRATEGI INTERNALISASI PENDIDIKAN RAGAM MODEL PEMERINTAHAN GEREJA BAGI GENERASI Z - Heru Cahyono; Rafles Ngilamele; Tony Suhartono (Bethel Press, 2021)
This study explores effective educational strategies to internalize the understanding of church governance systems for Generation Z. Focusing on their unique characteristics, such as digital skills, preference for interactive learning, and values of inclusiveness, this research proposes the integration of technology, active learning methods, contextual relevance, and practical leadership training. Through mobile applications, e-learning platforms, group discussions, simulations, and mentorship programs, Generation Z can acquire the knowledge and skills necessary to participate actively in church leadership. The results indicate that a holistic and integrated approach can equip Generation Z with the insights and abilities needed to manage and lead the church in the future.